Motivasi Berolahraga Terhadap Kebugaran Jasmani Siswa Kelas Viii Smpn 3 Bajo - Rachmat, Hidayat; Rafia, Febrianti; Rasyidah, Jalil (Jurnal Porkes, 2025)
The purpose of this study was to identify the relationship between exercise motivation and physical behavior of students in class VIII SMPN 3 Bajo. By using quantitative descriptive methodology. The population in this study were all 8th grade students of SMP Negeri 3 Bajo totaling 209 students divided into 8 classes. This study used purposive random sampling technique and totaled 45 students. The methods used for data collection are questionnaires and measurement tests. Descriptive analysis resulted in an average exercise motivation of 59.64 and physical fitness of 14.31. Data normality shows that both variables have a normal distribution. Regression analysis showed a positive and significant relationship between exercise motivation (variable X) and physical fitness motivation (variable Y) with a correlation coefficient (R) of about 0.762. Variable X has a significant influence on variable Y with a p-value of 0.000. The very high category includes 8 students (18%), high category includes 14 students (31%), medium category includes 18 students (40%), low category includes 5 students (11%), and very low category includes 0 students (0%).